Enriched Virtual Blended Learning Model Assisted by Digital Comics: Its Effect on Student Learning Motivation - Ryan Brilian Fatsena; Basori; Agus Efendi (Journal of Informatics and Vocational Education, 2024)
The Enriched Virtual Blended Learning model, assisted by digital comics, has attracted attention in the world of education for its positive influence on student motivation. This model requires students to study material both before and after class sessions. An experimental research method was used to determine the effect of this learning model on student motivation, as defined by four key indicators: "Feelings of Joy," "Student Involvement," "Interest," and "Student Attention." This experimental study proves that a significant change occurs when using this learning model. The results show a significance value (2-tailed) of 0.000, which is less than the significance level of 0.05. Thus, it is concluded that the application of the Enriched Virtual Blended Learning model assisted by digital comics has a significant influence on student learning motivation. By incorporating various factors that can increase student motivation, this model provides a positive influence on achieving learning objectives.